2018
DOI: 10.1038/s41598-018-27068-y
|View full text |Cite
|
Sign up to set email alerts
|

Climatic niche divergence drives patterns of diversification and richness among mammal families

Abstract: A major goal of evolutionary biology is to understand why clades differ dramatically in species richness. A key to this challenge is to uncover the correlates of variation in diversification rate (speciation – extinction) among clades. Here, we explore the relationship between diversification rates and the climatic niches of species and clades among 92 families of terrestrial mammals. We use a time-calibrated molecular phylogeny of mammals and climatic data from 3335 species. We show that considerable variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 64 publications
(117 reference statements)
8
52
3
Order By: Relevance
“…Additionally, our analysis revealed that niche rate and diversification rate are related at the family level of Urodela clades ( F 1,8 = 8.2, p = 0.02, R 2 = 0.44; Table S2), as previously reported for lower taxonomic levels (Kozak & Wiens, ). These observations are consistent with an extensive study showing a strong correlation between diversification rate and niche rate at family‐level clades in mammals (Castro‐Insua, Gómez‐Rodríguez, Wiens, & Baselga, ).…”
Section: Resultssupporting
confidence: 91%
“…Additionally, our analysis revealed that niche rate and diversification rate are related at the family level of Urodela clades ( F 1,8 = 8.2, p = 0.02, R 2 = 0.44; Table S2), as previously reported for lower taxonomic levels (Kozak & Wiens, ). These observations are consistent with an extensive study showing a strong correlation between diversification rate and niche rate at family‐level clades in mammals (Castro‐Insua, Gómez‐Rodríguez, Wiens, & Baselga, ).…”
Section: Resultssupporting
confidence: 91%
“…and B)(Purvis and Hector 2000, Jones and Safi 2011, Safi, Cianciaruso et al 2011, Davis, Faurby et al 2018). This observation is evident at the lower phylogenetic level of genus (not shown), indicating that species richness varies substantially between the different lineages throughout the Mammalia phylogenetic tree (Castro-Insua,Gómez-Rodríguez et al 2018, Upham, Esselstyn et al 2019.Muroids present a striking example of this unevenness. They comprise an estimated 1,620 species split between three lineages representing some 30 % of mammalian species richness (about 5,400 defined species).…”
mentioning
confidence: 90%
“…The ability to detect and measure karyotype differences has increased enormously over the past twenty years (Payseur andRieseberg 2016, Hua andMikawa 2018), resulting in a rapidly growing collection of high resolution datasets that allow detailed analyses of the relationships between genome evolution and other evolutionary variables including physiological traits (body size, metabolic rate), life-history traits (r vs K-strategists) and ecological traits (geographic ranges, niche rate, diversification rate and species diversity) (Castro-Insua, Gómez-Rodríguez et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…), and that patterns of physiological evolution are correlated with climatic niche shifts (e.g., Kozak and Wiens ; Castro‐Insua et al. ). However, we found that rates of thermal niche evolution were similar between island and mainland lineages, suggesting that this is not the case (Table ).…”
Section: Discussionmentioning
confidence: 99%